2018
DOI: 10.1590/1982-021620182042818
|View full text |Cite
|
Sign up to set email alerts
|

Orofacial myofunctional characteristics of oral and oronasal breathers

Abstract: Purpose: to compare the variables of the Orofacial Evaluation with Scores Protocol between nasal, oral and oronasal breathers. Methods: a sample consisting of three distinct groups subdivided into nasal, oral and oronasal breathers, both genders, with ages ranging from 6 to 12 years. The characteristics of the orofacial musculature were measured using the protocol. Results: there was a significant difference between oral and oronasal breathers compared to nasal ones (p=0.0007) in specific variables such as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The results of this study allow us to consider OB as a mild form of MB but not as a distinct pattern. This postulate is supported by some authors ( 12 , 14 , 19 , 23 ) . Yet, the high variability found in this study within the MB group suggest that the breathing pattern is best described as a general and predominant trend ( 16 , 17 ) and that MB should be viewed as a continuum within which exclusive mouth breathing is rare ( 12 ) .…”
Section: Discussionsupporting
confidence: 60%
“…The results of this study allow us to consider OB as a mild form of MB but not as a distinct pattern. This postulate is supported by some authors ( 12 , 14 , 19 , 23 ) . Yet, the high variability found in this study within the MB group suggest that the breathing pattern is best described as a general and predominant trend ( 16 , 17 ) and that MB should be viewed as a continuum within which exclusive mouth breathing is rare ( 12 ) .…”
Section: Discussionsupporting
confidence: 60%
“…21 The diminished muscle behavior in MB may be caused by the hypofunctioning of the masticatory muscles of these subjects, especially the mandibular elevators, as the mouth remains open for breathing. 5,8 The masticatory preference pattern and changed head posture of MBs can also interfere with the asymmetry of the musculature, though with no defined pattern. 16,40 Thus, it was hypothesized that the possible asymmetry in the masticatory muscles of this population can also interfere with muscle fatiguewhich, however, was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…These changes include mandible posture and occlusal changes and influences on the facial growth pattern. [5][6][7][8][9] Some studies have shown that MBs typically have an elongated face, 5 while others have found mesofacial 10,11 and brachyfacial growth patterns 12 as a characteristic of this population. All these imbalances may potentialize speech, 13 swallowing, 2,9 and mastication changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative evaluation of the tongue, although a routine in SLP practice, especially in the field of orofacial motricity, is still little studied, mainly regarding the performance of children (16) . Different studies addressing specific tongue tasks such as force (26) , mobility (27) , praxis (14,28,29) , and frenulum (22) have been conducted with individuals with varied clinical conditions. However, the present study innovates by investigating the association between the different tasks of tongue assessment.…”
Section: Discussionmentioning
confidence: 99%